2013
DOI: 10.1111/bju.12356
|View full text |Cite
|
Sign up to set email alerts
|

Laparoendoscopic single‐site (LESS) robot‐assisted nephroureterectomy: comparison with conventional multiport technique in the management of upper urinary tract urothelial carcinoma

Abstract: Objective• To compare the peri-operative, pathological and oncological outcomes of laparoendoscopic single-site (LESS) robotassisted nephroureterectomy (LESS-RALNU) with those of multiport robot-asssisted nephroureterectomy (M-RALNU). Patients and Methods• A total of 38 patients with upper urinary tract urothelial carcinoma underwent LESS-RALNU (n = 17) or M-RALNU (n = 21) by a single surgeon at a tertiary institution.• Data were obtained from a prospectively maintained database. Results• Patients' demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…This finding is consistent with a recent report assessing a cohort of 422 patients who underwent ONU, LNU, and RNU, demonstrating lower EBL for the robotic group [16]. Lower EBL translated into a lower transfusion rate, whereas ONU showed higher odds of transfusions (20%) [17]. LNU also had higher transfusion rate, but it was not clinically significant compared to RNU (11% vs 9%).…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with a recent report assessing a cohort of 422 patients who underwent ONU, LNU, and RNU, demonstrating lower EBL for the robotic group [16]. Lower EBL translated into a lower transfusion rate, whereas ONU showed higher odds of transfusions (20%) [17]. LNU also had higher transfusion rate, but it was not clinically significant compared to RNU (11% vs 9%).…”
Section: Discussionsupporting
confidence: 90%
“…This technique provided good control of the distal ureter, minimized the potential for tumor seeding. Lim 15 made a comparison between laparoendoscopic Single-Site (LESS) nephroureterectomy and conventional multiport technique in the management of UTUC. They concluded that LESS-nephroureterectomy might result in greater intra-operative blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper by Lim et al [1], patients were relatively homogenous between the two non-randomised arms. However, patients in LESS-RALNU cohort were significantly older (71 vs 62 years).…”
Section: Ralnu Was First Reported In 2006 and Since Then Multiple Gromentioning
confidence: 91%
“…In this small non-randomised prospective single-surgeon series, Lim et al [1] compare laparoendoscopic single-site robot-assisted nephrouretectomy (LESS-RALNU) with multiport RALNU (M-RALNU) for operative technique and oncological outcomes. The authors should be congratulated on reporting in an area of urology where there is paucity of data and techniques are constantly evolving.…”
Section: Robot-assisted Nephrouretectomy: Is Less More?mentioning
confidence: 99%
See 1 more Smart Citation